The NBN founder mutation—Evidence for a country specific difference in age at cancer manifestation. Issue 2 (10th August 2022) - Chrzanowska, Krystyna H.; Seemanova, Eva; Varon, Raymonda; Digweed, Martin; Piekutowska‐Abramczuk, Dorota; Sperling, Karl; Seeman, Pavel
Abstract: Background: Nijmegen breakage syndrome (NBS) is an autosomal‐recessive chromosome instability disorder characterized by, among others, hypersensitivity to X‐irradiation and an exceptionally high risk for lymphoid malignancy. The vast majority of NBS patients is homozygous for a common Slavic founder mutation, c.657del5, of the NBN gene, which is involved in the repair of DNA double‐strand breaks (DSBs). The founder mutation also predisposes heterozygous carriers to cancer, apparently however, with a higher risk in the Czech Republic/Slovakia (CS) than in Poland. Aim: To examine whether the age of cancer manifestation and cancer death of NBN homozygotes is different between probands from CS and Poland. Methods: The study is restricted to probands born until 1989, before replacement of the communist regime by a democratic system in CS and Poland, and a substantial transition of the health care systems. Moreover, all patients were recruited without knowledge of their genetic status since the NBN gene was not identified until 1998. Results: Here, we show that cancer manifestation of NBN homozygotes is at a significantly earlier age in probands from CS than from Poland. This is explained by the difference in natural and medical radiation exposure, though within the permissible dosage. Conclusion: It is reasonable to assume that this finding also sheds light on the higher cancer risk of NBN heterozygotes in CS than in Poland. This has implications for genetic counseling and individualized medicine also of probands with other DNA repair defects.